Hypnotherapy modulating early and late event-related potentials components of face processing in social anxiety - Zhang, Han; Xue, Xinrong; Wen, Jialin; Li, Yongyi; Fan, Chuan; Ma, Lijun; Wang, Huixue; Zhang, Mi; Zhang, Shuyu; Hu, Die; Wang, Kai; Li, Xiaoming (Frontiers in Psychiatry, 2024)
Background Hypnotherapy has a potential role in modulating attention bias to treat social anxiety disorder (SAD). This study aimed to verify whether hypnotherapy can reduce social anxiety by changing attentional bias. The primary objective of our study is to explore the influence of hypnosis on various aspects of attention processes, specifically focusing on how it affects attention bias and social anxiety. Methods This study included 69 participants with SAD who were assigned to three groups based on their scores on the Liebowitz Social Anxiety Scale (LSAS). The experimental group (n = 23) received a hypnosis treatment once a week, for a total of six sessions, while the control group (n = 23) and the baseline group (n = 23) did not receive any treatment. To evaluate whether hypnosis could alleviate SAD and attention bias towards threatening stimuli, we employed questionnaires and an odd-one-out task accompanied by electroencephalography (EEG) recordings. Results Under the attention sensitivity conditions, the experimental group exhibited a reduced N170 and LPP at the posttest stage, and a similar N170 and LPP reduction under the attention disengagement conditions. Notably, the symptom improvements were positively correlated with the reduction in N170 and LPP amplitude across conditions. Conclusion Hypnosis treatment modulates the early face processing and late emotional evaluation of threat-related stimuli in SAD patients. These findings suggest that N170 and LPP are important biomarkers for the treatment of SAD.